HERBIVOROUS FISH THAT ARE RAISED ON FISH FARMS IN THE BUKHARA REGION - Buriyev S. B.; Xodjiyeva M. S. (Scholars Digest Publishing, 2023)
This article provides information on the results of observations about herbivorous fish, widely cultivated in the Bukhara region, economically profitable, as well as on microphytes and macrophytes used to feed these fish.
Keywords: microscopic algae, macrophytes, VNIPRIX, silver carp, azolla, lemna, acclimatization, incubation, livestock.